Multi-stakeholder Dialogue Space Together Scaling Climate Smart Agriculture and Climate Information Services in Zambia - Concept Note - Mutenje, Munyaradzi; Pele, Winnie; Ngowenani, Nohayi; Jacobs-Mata, Inga; Minh, Thai Thi; Dahl, Hauke; Mapedza, Everisto D.; Homann-Kee Tui, Sabine; Ngwira, Amos R.; Mudege, Netsayi N.; Kakwasha, Keagan; Mudzungaire, Lizzy; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
AICCRA’s approach to facilitating CSA-CIS MSDs in Zambia is to interact with existing and relevant MSP through AICCRA CSA-CIS MSD Space at the regional, national level and sub national level. The CSA-CIS MSD Space is a physical and institutional space where members come together to exchange ideas and jointly explore opportunities to scale CSA-CIS innovations in specific agro-ecological contexts (Minh et al. 2020). Together, members in the CSA-CIS MSD Space enable the sustainable and inclusive scaling of CSA-CIS innovation bundles in key CSA value chain to benefit particularly lower part of the pyramid. Figure 1 illustrates the CSA-CIS MSD Space, presenting objectives, operational mechanism and thematic focus of collaboration with the intended new and existing groups of MSPs.